Implementasi Peraturan Bupati Pandeglang Nomor 28 Tahun 2019 tentang Percepatan Penurunan Stunting (Studi Kasus Desa Banjarsari Kecamatan Kaduhejo) - Indrawati, Erni; Cadith, Juliannes (Jurnal Sosial Politik dan Hukum, 2024)
Stunting is a problem of chronic malnutrition caused by insufficient nutritional intake over a long period of time due to the provision of food that does not meet nutritional needs. This research uses descriptive qualitative research methods. The qualitative approach was chosen because the data collected was natural. The aim of this research is to find out how to implement the Pandeglang Regency Regent's Regulation Policy Number 28 of 2019 concerning the Acceleration of Stunting Reduction (Case Study of Banjarsari Village, Kaduhejo District). The problems found in this research are the high stunting rate in Paandeglang Regency amounting to 29.4% in 2022, the discrepancy in the recapitulation data of stunting cases between those recorded at the Health Service and those at the health centers accessed via e-PPGM, lack of community participation and community support in participating in the Stunting reduction program, lack of supervision and monitoring from the Health Service and Community Health Centers, lack of understanding and public awareness about the importance of balanced nutrition for children's growth and development. The theory used is the Implementation theory from Van Metter and Horn. From this research it is known that in implementing the Pandeglang Regent Regulation Number 28 of 2019 concerning the Acceleration of Stunting Reduction (Case Study of Banjarsari Village, Kaduhejo District) it can be said that the results are quite good but there are still deficiencies and obstacles in its implementation that prevent stunting reduction programs from running optimally. This is caused by several obstacles, namely the social conditions of the community, the habits of the community, the availability of a budget that is not yet fully adequate, the understanding of some implementers is still not optimal, then regarding the targets, everything is already in this Regent's Regulation, but in its implementation there are still data inconsistencies. data in the field.